Factors associated with tetanus vaccination in peruvian pregnant women: ENDES 2021 - Corimanya, Diana (2023)
Objective: To determine the factors associated with compliance with tetanus vaccination in Peruvian pregnant women according to ENDES 2021. Materials and methods: Cross-sectional and analytical study. The demographic and family health survey (ENDES) 2021 was analyzed. Women aged of 12 and 49 who were pregnant or had been pregnant in the last year were included. Results: A higher prevalence of the complete tetanus vaccination was found in the age group of 35-49 years (PRa = 1,348 [ 95% I.C.; 1,144 - 1,588]), 20 to 34 years (PRa = 1,337 [ 95% I.C. 1,146 - 1,560] ), originating from Metropolitan Lima (PRa = 1,209 [ 95% CI; 1,078 – 1,356]), the coastal region (PRa = 1,318 [ 95% CI; 1,190 – 1,460]), jungle (PRa = 1,440 [ 95% CI; 1,271 – 1,631]) the wealthiest income quintile (PRa = 1,110 [ 95% CI; 1,014 - 1,216]), having health insurance (RPa = 1,108 [ 95% CI; 1,029 - 1,194]), receiving care from a nurse ( PRa = 1,172 [ 95% CI; 1,065 - 1,289), receiving care from an obstetrician (PRa = 1,172 [ 95% CI; 1,065 - 1,289) and having 6 or more prenatal check-ups (PRa = 1,724 [ 95% CI; 1,567 - 1,897 ). Conclusions: The factors independently associated with compliance with tetanus vaccination in in pregnant women in Peru were age, originating from Metropolitan Lima, the coast region, the jungle, the wealthiest income quintile, having health insurance, receiving care from a nurse, receiving care from an obstetrician, and having more than six prenatal check-ups.